Effects of Ramiprilat-Coated Stents on Neointimal Hyperplasia, Inflammation, and Arterial Healing in a Porcine Coronary Restenosis Model - Hong, Young Joon (The Korean Society of Cardiology, 2011)
BACKGROUND AND OBJECTIVES: The renin-angiotensin-aldosterone system has been implicated in the pathogenesis of neointimal hyperplasia, and a role for angiotensin II in the migration and proliferation of vascular smooth muscle cells in restenotic lesions has been proposed. The aim of this study was to determine the anti-proliferative and anti-inflammatory effects of ramiprilat-coated stents in a porcine coronary overstretch restenosis model. SUBJECTS AND METHODS: Pigs were randomized into two groups in which the coronary arteries {16 pigs (16 coronaries in each group)} had a 3.0×17 mm ramiprilat-coated MAC stent or a 3.0×17 mm control MAC stent (AMG, Munich, Germany) implanted with oversizing (stent-to-artery ratio, 1.3 : 1) in porcine coronary arteries, and histopathologic analysis was assessed 28 days after stenting. RESULTS: There were no significant differences in the injury and inflammation scores between the two groups (1.20±0.43 vs. 1.23±0.57, p=0.8; and 1.21±0.39 vs. 1.25±0.49, p=0.6, respectively). Within the neointima, most inflammatory cells were lymphohistiocytes. Significant positive correlations existed between inflammatory cell counts and the neointima areas (r=0.567, p<0.001), and between inflammatory cell counts and the percent area stenosis (r=0.478, p<0.001). There was no significant difference in the inflammatory cell counts normalized to the injury (110±89 vs. 123±83, p=0.4) and fibrin scores (0.15±0.06 vs. 0.17±0.07, p=0.8) between the 2 groups. There were trends toward a smaller neointima area (1.06±0.51 mm(2) vs. 1.28±0.35 mm(2), p=0.083) and a smaller percent area stenosis (18.9±8.7% vs. 21.8±7.2%, p=0.088) in the ramiprilat-coated stent group. CONCLUSION: Although the ramiprilat-coated stent did not show significant inhibitory effects on neointimal hyperplasia, the ramiprilat-coated stent showed good effects on the inflammatory reaction and arterial healing similar to the control stent in a porcine coronary restenosis model.